Scintigraphic evaluation of multifocal osteolytic lesions in a patient with primary hyperparathyroidism: A case report - Ristevska, Nevena; Stojanoski, Sinisa; Pop Gjorcheva, Daniela; Angjeleska Meri (My University, 2015)
Osteitis fibrosa cystica is the classic patognomonic form of skeletal disease in hyperparathyroidism that characterizes with decreased cortical bone thickness compared to increased cancellous bone. We present a case of 52-year old female patient with osteolysis of the left calf on radiographic images. The bone scan detected multiple focal pathological accumulations in the skull, left tibia, both femurs and in the left ischium. The scan was indicative of secondary multiple skeletal metastases. Because the patient had no previous history of primary malignant disease, metabolic bone disease was suspected and also confirmed after i.v application of 99mTc-MIBI. The scan was in favor of parathyroid adenoma with bone complication (osteitis fibrosa cystica). Neck ultrasonography revealed hypoechoic oval mass below the left lower thyroid lobe that suggested the possibility of parathyroid adenoma. An increased ionized calcium level and PTH confirmed the diagnosis of primary hyperparathyroidism. Parathyroidectomy with radioguided surgery was performed. Hyperparathyroidism is a curable disease and a clinician should always bear in mind a metabolic bone disease when performing a nuclear bone scan where multiple bone lesions are detected (a hallmark of metastatic disease).
Keywords: parathyroid adenoma; 99mTc-MIBI; scintigraphy; PTH